PENGUATAN KETERAMPILAN BERPIKIR TINGKAT TINGGI SISWA MELALUI PEMBELAJARAN BAHASA BERBASIS AKTIVITAS: PENGALAMAN PROGRAM PLP II DI SMAN 6 SIDRAP - Syahrir L; Syamsunir; Muhammad Takdir; Firman; Nurul Faradillah; Riska Dwi Apriani (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
The School Field Introduction Program (PLP) II is a strategic phase in preparing prospective professional teachers while strengthening university–school partnerships. At UPT SMAN 6 Sidrap, PLP II was implemented from 1 October to 30 November 2025 by a field supervising lecturer and four students from Indonesian Language Education and English Language Education study programs. The activities focused on activity-based language learning assistance oriented toward higher order thinking skills (HOTS) in grade XI and XII classes. Together with mentor teachers, the students designed and implemented lessons on descriptive text, exposition text, hikayat, and pantun through role play, debates, game-based learning, writing tasks, and the use of video media. Data were collected through classroom observations, daily activity logs, reflective notes, and documentation, then analyzed using a descriptive qualitative approach. The results indicate that varied activity-based strategies increased student engagement and fostered the abilities to analyze, evaluate, and create in language learning, in line with HOTS characteristics. At the same time, the students gained authentic experience in designing learning tools, managing classrooms, and conducting reflection, thereby strengthening their pedagogical competence. These findings suggest that PLP II can be developed as a community service model based on school–university partnership to enhance language learning at the senior high school level.